Trends of Thailand Healthcare Service System - Phalitnonkiat, Passarin -; Wongsuttilert, Alisara; Kunnapapdeelert, Siwaporn (Business Administration and Management Journal Review, 2021)
Currently, Thai government is supporting Thailand to be an international medical hub. Thailand healthcare services are expanding to the CLMV nations, China, Russia and Africa. Subsequently, the numbers of foreign patients that come to Thailand for treatment will trend to be increased. Healthcare becomes one of the fast-growing sectors in Thailand. Thailand is recognized as the highest level of preparedness to cope with epidemics in Asia, based on the Global Health Security (GHS) Index 2019. Thailand has received 92.58 for the infrastructures, 96.22 for the cost, 89.91 for government readiness, 67.51 for medicine availability, and 17.37 for the professional competence. These enhance Thailand healthcare services system to be developed for facing more intense competition both domestically and internationally. It is interesting to understand Thailand healthcare services situation for enhancing Thailand’s competitiveness and potential to be a center of the regional economy in the future. This article emphasizes on the trends of healthcare services systems in Thailand. Encouragement for Thai people to increase their longevity is described in the first section. Data warehousing for healthcare is then explained. Later, technology for healthcare industry transformation is mentioned as the third issues. The leveraging business intelligence for healthcare management is then proposed. Lastly, trend of wellness tourism in Thailand is discussed in the last section.